Uniform Compact Attractors for a Nonlinear Non-autonomous Equation of Viscoelasticity (Journal of Partial Differential Equations, 2009)
In this paper we prove the regularity, exponential stability of global solutions and existence of uniform compact attractors of semiprocesses, generated by the global solutions, of a two-parameter family of operators for a nonlinear one-dimensional non-autonomous equation of viscoelasticity. We employ the properties of the analytic semigroup to show the compactness for the semiprocess generated by the global solutions.